1996
DOI: 10.1029/96gl00621
|View full text |Cite
|
Sign up to set email alerts
|

Neon‐20, oxygen‐16, and helium‐4 densities, temperatures, and suprathermal tails in the solar wind determined with WIND/MASS

Abstract: Measurements from the MASS instrument on the WIND spacecraft from late Dec. 94 through Aug. 95 are reported for 20Ne, 16O, and 4He. The average 4He/20Ne density ratio is 566±87 with considerable variability. The average 16O/20Ne density ratio is 8.0±0.6 and is independent, within experimental uncertainty, of solar wind speed. The 20Ne/4He and 16O/4He temperature ratios at the lowest solar wind speeds are consistent with unity, increasing with increasing speed to values exceeding that expected from mass proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 16 publications
(3 reference statements)
6
118
0
Order By: Relevance
“…Their value is possibly somewhat biased towards abundances in low-speed solar wind. Collier et al (1996) obtained similar values with WIND/MASS for in-ecliptic solar wind for a period of relatively low solar activity from December 1994 through August 1995. They find [Ne/O] = 0.14 ± 0.01 and no significant dependence of this ratio from the solar wind speed.…”
Section: H I Given Insupporting
confidence: 68%
See 2 more Smart Citations
“…Their value is possibly somewhat biased towards abundances in low-speed solar wind. Collier et al (1996) obtained similar values with WIND/MASS for in-ecliptic solar wind for a period of relatively low solar activity from December 1994 through August 1995. They find [Ne/O] = 0.14 ± 0.01 and no significant dependence of this ratio from the solar wind speed.…”
Section: H I Given Insupporting
confidence: 68%
“…Relating the oxygen abundance of the solar wind to the helium abundance gives a consistent picture: Bochsler et al (1986) find [He/O] = 75 ± 20, whereas Collier et al (1996) find [He/O] = 70 ± 6. The averages of Collier et al (1996) are shown in Fig.…”
Section: H I Given Inmentioning
confidence: 66%
See 1 more Smart Citation
“…2c). The power-law tails at high-energy parts of ion spectra in space plasmas are long known (Montgomery et al 1968;Collier et al 1996), the powerlaw exponent of ∼ −5 is often detected in ion velocity distribution in space (Gloeckler 2003). During our simulation such tail is formed only for a narrow range of velocities (Fig.…”
Section: Evolutionmentioning
confidence: 98%
“…Collier et al [1996] fit kappa distributions to both fast and slow solar wind using WIND data. Also using WIND data, Chotoo et al [2000] analyzed power law tails associated with corotating interaction regions and extracted the values of k. The 2004 Voyager 1 termination shock crossing extends suprathermal tail observations into the heliosheath.…”
Section: Introductionmentioning
confidence: 99%